The comparison of the results of laser scanning and classical surveying methods of measuring the area and volume in the chapel of St. Kinga in the salt mine of Bochnia - Maciaszek, Jadwiga Maria; Madusiok, Dominik; Matwij, Wojciech (Geology, Geophysics and Environment, 2013)
Providing a long durability of the historic salt mine of Bochnia demands proper observations, analyses and drawing conclusions based on them and leading to recognising and the assessment of a specific behaviour of the rock mass and the effectiveness of the protection from mining damage. The studies of the rock mass and surface deformation are carried out by the mine based on the results of the observations made with the methods of surveying. These observations include, among others, the measurements of the height of benchmarks stabilized on the surface and rock mass, the measurements of linear convergence (on the established vertical and horizontal bases in selected chambers of the mine); and since 2003 the attempts have been made to apply total stations and laser scanners to document the selected chambers. The article presents test studies on laser scanning carried out in the chapel of St. Kinga in the Bochnia Salt Mine in 2007 and 2013 (Fig. 1). They showed high accuracy of the scanning method both in the positioning of points of the salt excavation, in modelling, as well as calculation of the area of any cross-section (Fig. 2) and the volume of chambers of complicated shapes (Fig. 3). The carried out accuracy studies, analyses and comparisons were used in the calculation of the area convergence for the chapel of St. Kinga in the Bochnia Salt Mine. They make base for the calculation of volume do convergence in the near future.